Alfalfa silage vs. alfalfa hay for wintering heifer calves - Baker, F.H.; Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Twenty choice-quality Hereford heifer calves, average weight of 4.38 pounds each, were used. The heifers were purchased as calves from the Lonker and the Hall-McNally ranches in Barber county, Kansas. Allotment of the heifers was based on weight, feeder grade, and origin. The alfalfa hay and silage were harvested from the first-cutting growth on the Animal Husbandry farm. The silage was allowed to wilt from one to two hours in the harvesting process. In the feeding trial, 3 pounds of alfalfa hay was fed to the cattle of Lot 3 to provide readily available protein and dry roughage. The heifers of Lot 3 were maintained at maximum consumption of alfalfa silage, whereas the heifers of Lot 6 were restricted to the same dry matter intake as Lot 3.
Keywords: Beef; Alfalfa silage vs. alfalfa hay; Dry matter intake; Roughage